Human Platelets Contain Scinderin, a Ca2+-Dependent Actin Filament-Severing Protein - Rodríguez Del Castillo, A; Vitale, M L; Tchakarov, L; Trifaró, J-M (Thrombosis and Haemostasis, 1992)
A large body of biochemical and morphological evidence suggests that actin polymerizes in response to various stimuli which activate platelets. Previous work has shown the presence in platelets of gelsolin, a Ca2+-dependent regulator of actin filament length. This present work demonstrates that human platelets contain scinderin, another Ca2+-dependent actin filament-severing protein recently discovered in our laboratory. Extracts prepared from platelets were subjected to DNase-I-Sepharose 4B affinity chromatography. EGTA eluates from the affinity columns contained scinderin as demonstrated by mono and two-dimensional polyacrylamide gel electrophoresis and immunoblotting with scinderin antibodies. The concentration of scinderin in platelets was 75 fmol/mg total protein. This might represent 11% of the total actin filament-severing activity if both proteins are equally potent, on a molar basis, in severing actin filaments. Double staining immunocytochemical studies with antibodies against scinderin and rhodamine phalloidin, a probe for F-actin, also demonstrated the presence of scinderin in platelets. These findings suggest that scinderin may participate in the regulation of platelet actin networks.